Ethyl 2-(3,5-difluorophenyl)quinoline-4-carboxylate: a second triclinic polymorph - S. Shashidhar Bharadwaj; Karthik Kumara; Boja Poojary; H. S. Yathirajan; K. Byrappa; N. K. Lokanath; S. Madan Kumar (IUCrData, 2016)
The title compound, C18H13F2NO2, is a polymorph of the structure reported by Sunitha et al. [Acta Cryst. (2015), E71, o341–o342]. Both compounds crystallize in the triclinic space group P\overline{1}. The principal difference between the two polymorphs lies in the orientation of the carboxylate substituents with respect to the planes of the quinoline ring systems. In the crystal, the packing features C—H...O hydrogen bonds together with short C—F...π and π–π interactions [inter-centroid distances of 3.8199 (11), 3.6825 (12) and 3.8722 (13) Å].